Application of the Principles of Landscape Ecology in Land Consolidation Engineering - Xiong, Yufei (Journal of physics. Conference series, 2021)
Through the application of land consolidation, can greatly improve the rural land pattern, so that its land use efficiency can be continuously improved, which has an important role in the improvement of people’s living standards, is the current we must pay attention to the content. But from a practical point of view, in the practice of land consolidation, there are still a variety of problems, many ecological environment related factors are not paid attention to, resulting in many unnecessary losses, hinder the sustainable development of the economy. As a new interdisciplinary subject, the application of landscape ecology in land consolidation can play a huge role, which is the necessary guarantee to improve the effect and value of land consolidation.